Assessing effects of personal behaviors and environmental exposure on asthma episodes: a diary-based approach - Chan, Ta-Chien (BMC Pulm Med, 2019)
BACKGROUND: Quantifying the effects of personal health behaviors and environmental exposure on asthma flare-ups is a challenge. Most studies have focused on monitoring the symptoms and drug usage for relieving symptoms. In this study, we emphasize the need to understand how personal and environmental conditions are related to the occurrence of asthma symptoms. METHODS: We designed an online health diary platform to collect personal health behaviors from children, their parents and other adults with any allergic diseases including asthma, allergic rhinitis, atopic dermatitis and allergic conjunctivitis. The participants used mobile devices or computers to record their daily health-related activities such as sleep, exercise, diet, perception of air quality and temperature, and asthma symptoms. The participants also recorded secondhand smoke exposure and the time of activities, which were combined with ambient air quality measurements for calculating personal air pollution exposure. A generalized linear mixed model was used to estimate the effects of the factors. RESULTS: During the study period (January 2017–June 2017, and October 2017–September 2018), 132 participants provided 25,016 diary entries, and 84 participants had experienced asthma symptoms in 1458 diary entries. The results showed some different risk factors for the minors and adults. For minors, high-intensity exercise, contact with persons with influenza-like illness (ILI) and the perception of hot temperature and bad indoor air quality were associated with the occurrence of asthma episodes. The identified risk factors for the adult participants included having dehumidifiers at home, exposure to secondhand smoke, having bad sleep quality, contact with persons with ILI, not eating fruit and seafood, perceiving cold temperature, bad quality of indoor and outdoor air, and exposure to high concentration of ozone. CONCLUSIONS: The revealed personal risk factors and perceptions of air quality and temperature may provide guidance on behavioral change for people susceptible to asthma to help control acute onset and severe exacerbation of asthma flare-ups.